Effectiveness of Traditional Remedies Pucuk Jarak and Bedak Langeh in Melongas Massage on the Growth and Development of Stunted Toddlers - Widani Darma Isasih; Junendri Ardian (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Stunting is a serious health problem among toddlers, characterized by delayed physical growth due to inadequate nutrition, a history of infectious diseases, low maternal education, and suboptimal parenting. In North Lombok Regency, the prevalence of stunting remained high at 19.3% in 2023. Efforts to address this issue have not only focused on nutritional interventions but also included complementary non-pharmacological therapies, such as melongas massage, which has been traditionally practiced using pucuk jarak and bedak langeh remedies. This study aimed to examine the effectiveness of these two remedies on the growth and development of stunted toddlers. A quasi-experimental nonequivalent control group design was applied, involving 72 stunted toddlers divided into three groups: pucuk jarak, bedak langeh, and control. The intervention was carried out for four weeks with melongas massage administered twice weekly. The measured parameters included body weight, height, appetite, sleep quality, and immune function. The results showed that the pucuk jarak group experienced more significant improvements across all parameters compared to the bedak langeh and control groups. Phytochemical tests supported these findings, showing total flavonoid levels of 53.32 mgQE/g in pucuk jarak compared to 3.58 mgQE/g in bedak langeh. The high flavonoid content is believed to play an important role in improving metabolism, appetite, growth, and immunity in toddlers. Thus, melongas massage using pucuk jarak has the potential to serve as a complementary strategy rooted in local wisdom for accelerating stunting reduction programs in North Lombok.